S113 Pulmonary drug-resistant tuberculosis and surgery: report of 39 patients treated in a tertiary care hospital in mumbai. (12th November 2019) - Intini, E; Mullerpattan, J; Kishore, G; Malu, K; Rana, D; Sarkar, T; Wagh, H; Ganatra, S; Amale, R; Udwadia, ZF
Abstract : Background: Drug resistant pulmonary TB has poor outcomes despite prolonged treatment. Surgery is an option in DR-PTB patients with localized cavitary disease having adequate pulmonary reserve. 1 Methods: This is a retrospective analysis of patients with pulmonary DR-TB who underwent lung resection surgery between 2007 and 2018 at a single private tertiary care hospital in Mumbai. All patients received chemotherapy preoperatively and postoperatively. The indications for surgery included failure of medical treatment or persistent cavity with high probability of relapse. Patient demographic data, clinical characteristics, surgical procedures and surgical outcomes were studied. Results: A total of 39 patients were enrolled from a single private hospital in Mumbai. Of these, there were 26 female and 13 males, with a mean age of 31 years and a mean BMI of 17 kg/m2. DR-TB was diagnosed on culture and drug susceptible test, showing 13 had XDR-TB, 19 had MDR-TB + fluoroquinolone resistance and 7 had MDR-TB. The lung involvement was evaluated on Chest CT scan, using the Timika Score. 61% of patients presented a left lung involvement, 35% right involvement and 69% had cavities. The type of surgery performed is given in the table 1. For outcome evaluation, culture status post-surgery and at the end of treatment were considered. A positive outcome was shown in 58% of patients, in particular 46% among XDR- TB cases, 68% in pre-XDR group and 71% in MDR-TB. Postoperative complications were observed in 4 patients only; 2 showed surgical wound infection and 1 patient had the left vocal cord palsy. One patient had a bronchopleural fistula post left pneumonectomy for which he required thoracoplasty. Conclusions: As the numbers of drugs need to treat DR-TB are limited, surgery has an important adjunctive role. Pulmonary resection in combination with appropriate chemotherapy in carefully selected patients appears to be an effective measure with improved outcomes. Reference: Russell R Kempker, Sergo Vashakidze, Nelly Solomonia, Nino Dzidzikashvili, Henry M Blumberg, Surgical treatment of drug-resistant tuberculosis, Lancet Infect Dis 2012; 12:157–66